Measles antibody levels among vaccinated and unvaccinated children 6–59 months of age in the Democratic Republic of the Congo, 2013–2014. Issue 9 (24th February 2020) - Ashbaugh, Hayley R.; Cherry, James D.; Hoff, Nicole A.; Doshi, Reena H.; Alfonso, Vivian H.; Gadoth, Adva; Mukadi, Patrick; Higgins, Stephen G.; Budd, Roger; Randall, Christina; Mwamba, Guillaume Ngoie; Okitolonda-Wemakoy, Emile; et al.
Abstract: Background: Measles is endemic in the Democratic Republic of the Congo (DRC), and 89–94% herd immunity is required to halt its transmission. Much of the World Health Organization African Region, including the DRC, has vaccination coverage below the 95% level required to eliminate measles, heightening concern of inadequate measles immunity. Methods: We assessed 6706 children aged 6–59 months whose mothers were selected for interview in the 2013–2014 DRC Demographic and Health Survey. History of measles was obtained by maternal report, and classification of children who had measles was completed using maternal recall and measles immunoglobulin G serostatus obtained from a multiplex chemiluminescent automated immunoassay dried blood spot analysis. A logistic regression model was used to identify associations of covariates with measles and seroprotection, and vaccine effectiveness (VE) was calculated. Results: Out of our sample, 64% of children were seroprotected. Measles vaccination was associated with protection against measles (OR: 0.15, 95% CI: 0.03, 0.81) when administered to children 12 months of age or older. Vaccination was predictive of seroprotection at all ages. VE was highest (88%) among children 12–24 months of age. Conclusion: Our results demonstrated lower than expected seroprotection against measles among vaccinated children. Understanding the factors that affect host immunity to measles will aid in developing more efficient and effective immunization programs in DRC.